Usabilidade e eficiência do pre1Brazil, um web aplicativo para suporte de estudo clínico de intervenção com alogliptina em pacientes portadores de Diabetes Melittus Tipo1 estágio 2 - Saboia, Jaquellyne Gurgel Penaforte (2022)
Type 1 diabetes mellitus (T1DM) results from an autoimmune injury against beta pancreatic cells. The development of multiple autoantibodies is considered the first stage of the disease. Stage 2 is characterized by autoimmunity associated with asymptomatic glucose intolerance. Symptoms defines stage 3. Currently, there is no safe and effective therapy capable of interrupting the autoimmune process. Barriers to implement prevention trials, such as underdiagnosis and high costs, difficult therapeutic advances. The use of computer technology can be helpful in overcoming these challenges, increasing the reach of isolated groups, provides faster and lesser costs trials with more agile recruitment. PRE1BRAZIL is an easy and intuitive web application (APP) designed to remotely conduct, unify and standardize a homonym clinical trial. The ECT protocols guided the design of non-functional APP requirements. A usercentered development approach was used. The APP functional project was divided into two components: the web questionnaire, where patients' data will be entered; and the Web Control Panel (WBC) that will display and export the data to a spreadsheet. FrontEnd, BackEnd, and Database are the three WBC components. After web APP design and development, a validation study was performed with 20 evaluators. The validation test results showed a high usability and efficiency of the APP, with high agreement rating between expert judges and target users. This APP is able to support all ECT phases, from enrollment and randomization to report adverse events. This APP was developed to support a longitudinal, multicenter, randomized, openlabel, homonymous study of clinical intervention with aloglipitin, an inhibitor of enzyme Dipeptil Peptidase 4 (iDDP-4) in patients aged 18 to 35 years with stage 2 T1DM. The outcome will be the rate of progression to stage 3 T1DM at the end of 2 years of follow-up between the treatment (alogliptin 25mg/day) and control groups. The iDDP-4 are safe and potentially effective drugs in the early stages of T1DM. The enzyme plays a fundamental role in the activation and proliferation of T cells. Several studies demonstrate an increase in its activity in patients with T1DM. Its inhibition can suppress the proliferation of T cells, the production of Th1 cytokines and stimulate the secretion of the TGF-β1 growth factor, which is essential in the regulation of autoimmunity. At PRE1BRAZIL, the clinical trial procedures (from enrollment to adverse events notifications) will be done through the APP. This way, it is expected to increase the participation of physicians and, consequently, of patients, a challenge in studies evaluating low-prevalence diseases. To reduce the high dropout rates, as well as inaccurate data, more frequent in online studies, we chose to develop an APP aimed at the researcher.This is the first web APP developed and validated to support a fully automated T1DM prevention trial. This APP is expected to optimize patient allocation, data analysis, and